(untitled) (Journal of Geography and Environmental Management, 2020)
The article is devoted to the development of the scientific historical interactive map “The People of Kazakhstan”, using geoinformation and WEB technologies. The main objective of the interactive map is, through the creation of historical and graphic maps and the accompanying scientific and reference material, to reveal and highlight the consolidating role of the Kazakh nation, aimed to establishing social harmony, establishing interethnic peace, developing national unity and strengthening tolerance on ancient Kazakh land. The important place on the Map is occupied by the Kazakhstan model of social harmony and national unity, reflecting the processes of modernization of the public consciousness of Kazakhstan people, the spiritual renewal of the Nation. The article describes the performed research work on the development and implementation of the scientific historical interactive map “People of Kazakhstan” in the form of an extensive information resource that provides for the systematization and collection of information on the historical periods of Kazakhstan’s development into a single geodatabase. Description of the technical aspects of the Map implementation, development and vision of the concept, structure of the project are provided, and information on the main components of the interactive map system is provided. The interactive historical map “The People of Kazakhstan” is intended to demonstrate the general context of the formation events of the people of Kazakhstan, the tendencies of its formation in time and space, the process of uniting the ethnic groups of Kazakhstan into one People.